Marine litter-fauna interactions: a standardised reporting framework and critical review of the current state of research with a focus on submarine canyons - Bruemmer, Alice Lauren; Dissanayake, Awantha; Davies, Jaime Selina (Frontiers in Marine Science, 2023)
Litter is ubiquitous in the ocean, interacting with fauna and causing impacts that are unquantified at present. Mainly sourced from land, marine litter is very persistent, and undergoes slow degradation upon settling on the ocean floor. Submarine canyons contain more litter than other oceanographic features due to hydrological processes, but study of litter in canyons is made difficult by logistical requirements. Monitoring and quantification of marine litter often do not consider interactions between fauna and litter, meaning impacts are largely unconsidered and unknown. Among publications that have reported litter-fauna (L-F) interactions in canyons, the large majority occur in the Mediterranean Sea, and the most reported interaction is of corals entangled in fishing gear. When it occurs, the reporting of L-F interactions is unstandardised, resulting in a lack of global comparison and trend analysis. A standardised, comprehensive framework for the reporting of L-F interactions has been created and includes 6 major categories: entanglement, ingestion, smothering, habitat provision, adaptive behaviour, and encountering (entanglement and smothering occur on abiotic features as well). Use of the framework will aid in research collaboration and creation of a global dataset of L-F interactions. Impacts resulting from interactions are plentiful, most coming from entanglement and smothering.